Decoding the Mantra of Succession Planning for the Unorganized Retail Stores in Central India - Verma, Shiladitya; Chatterjee, Ravi; Sen, Sujoy (Indian Journal of Marketing, 2017)
Purpose: The paper intended to study the unorganised retail sector in Central India related to their preparedness towards succession planning. Also, the paper tried to explore the family dynamics shared between the family members of a business. Design/Methodology/Approach: Literature was studied to analyze the various aspects related to succession planning. Bhopal being one of the growing markets having great potential has been the centre of the study. Empirical data were gathered from 138 family businesses of Bhopal using the questionnaire method. Findings: Evidences were found justifying the gap existing in the succession planning in the family owned businesses in Central India. Research Limitations/Implications : The study being conducted by taking 138 family-owned businesses limits the possibility of generalizability of the data. Practical Implications: The insights can be used by the family-owned unorganized retail stores in Bhopal to work out a systematic way of succession planning and avoid all the pitfalls to a successful venture. Originality/Value: The paper is one of its kinds as the empirical data being collected represents family-owned businesses of Bhopal and elucidates the present scenario of succession planning among them.